Spin-driven symmetry breaking in the frustrated fcc pyrite MnS2. (19th May 2015) - Kimber, Simon A J; Chatterji, Tapan
Abstract: We report the characterisation of natural samples of the cubic pyrite mineral MnS2 using very high resolution synchrotron x-ray diffraction techniques. At low temperatures we find a new low temperature polymorph, which results from coupling between magnetic and lattice degrees of freedom. Below the magnetic ordering temperature T N = 48 K, we detect a pseudo-tetragonal distortion with a tiny c / a ratio of 1.0006. The structure can be refined in the space group Pbca The symmetry lowering reduces magnetic frustration in the fcc Mn 2+ lattice and is likely responsible for the previously reported lock-in of the magnetic propagation vector. This behaviour is similar to the spin-Peierls phase transitions reported in other three-dimensional Heisenberg magnets like the chromate spinels.